Rocky 5 - Avildsen, John G. (Pasig City : Viva Video.)
After Rocky (Stallone) returns home from his latest triumph, he learns that all his money has been lost by an unscrupulous financial advisor. To make matters worst, his fight-related injuries force his retirement from the ring. So Rocky, his wife Adrian (Talia Shire) and his son Rocky Jr. (Sage Stallone) move to their low-rent neighborhood in South Philadelphia. There Rocky must resolve the deep-rooted resentment held by his son, a bitterness that grows when Rocky trains Tommy Gunn (Tommy Morrison), a young boxer who soon rises to national prominence. When Tommy turns against his mentor and publicly taunts him, Rocky knows he must fight once more.